EPJ quantum technology - Società italiana di fisica; EDP Sciences; Springer (Firm) (Springer-Verlag, GmbH, 2014)
Covers theoretical and experimental advances in subjects including but not limited to the following: quantum measurement, metrology and lithography; quantum complex systems, networks and cellular automata; quantum electromechanical systems; quantum optomechanical systems; quantum machines, engineering and nanorobotics; quantum control theory; quantum information, communication and computation; quantum thermodynamics; quantum metamaterials; the effect of Casimir forces on micro- and nano-electromechanical systems; quantum biology; quantum sensing; hybrid quantum systems.
Keywords: Quantum theory : Periodicals; Quantum computers : Periodicals; Information theory : Periodicals; Information theory; Quantum computers; Quantum theory; Atomic Physics